Shear bond strength of new and rebonded orthodontic brackets to the enamel surfaces - Salama, Fouad (J Orthod Sci, 2018)
OBJECTIVES: The objective of this study was to compare the shear bond strength (SBS) of new and rebounded orthodontic brackets bonded to the buccal sound and cleaned enamel surfaces using two orthodontic adhesives: resin-modified glass-ionomer (RMGI) and resin-composite. MATERIALS AND METHODS: Forty premolars were randomly allocated into four groups, 10 teeth/group. New and rebonded brackets were bonded to sound and cleaned enamel surface, and then were subjected to thermocycling. The bond strength was determined using a universal testing machine at a crosshead speed of 1 mm/min. Remaining adhesives on enamel after bracket debonding was scored independently by two investigators who were not aware of the four different groups, using adhesive remnant index (ARI). RESULTS: There was a statistical significant difference in SBS of the four groups (P = 0.005). SBS values were significantly higher with cleaned enamel surfaces after adhesive removal compared to sound enamel. SBS was significantly higher for rebonded brackets, when compared with the new brackets. No significant difference was found between the two adhesives types. The level of agreement between the two raters was higher toward the classification of higher categories of ARI (scores 5 and 6) with agreement percentage 91.7% and 100%, respectively. There was more adhesive remained among resin-composite groups. CONCLUSIONS: The bond strength of debonded sandblasted stainless-steel brackets was higher than new brackets. Resin-composite and RMGI orthodontic adhesives used in this study exhibited sufficient SBS values for bonding brackets to sound and cleaned enamel and comparable to each other.